2022
DOI: 10.1007/s40620-021-01206-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID–19 and chronic kidney disease: an updated overview of reviews

Abstract: Background Coronavirus disease (COVID–19) has resulted in the death of more than 3.5 million people worldwide. While COVID–19 mostly affects the lungs, different comorbidities can have an impact on its outcomes. We performed an overview of reviews to assess the effect of Chronic Kidney Disease (CKD) on contracting COVID–19, hospitalization, mortality, and disease severity. Methods We searched published and preprint databases. We updated the reviews by searching for prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 143 publications
8
100
1
3
Order By: Relevance
“…Based on previous studies, CKD increases the risk of mortality for COVID-19 patients by 5.81 times as the level of pro-inflammatory cytokines increases in CKD patients, causing an increase in oxidative stress which ultimately results in an immune-inflammatory response. The resulting immune system damage may increase susceptibility to bacterial and viral infections, and this may be the main reason for the increased risk of pulmonary inflammation [ 19 , 20 ]. Based on previous research, it was stated that T2DM had a significant relationship with the mortality of COVID-19 patients, where T2DM patients infected with COVID-19 had a mortality risk of 1.75 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, CKD increases the risk of mortality for COVID-19 patients by 5.81 times as the level of pro-inflammatory cytokines increases in CKD patients, causing an increase in oxidative stress which ultimately results in an immune-inflammatory response. The resulting immune system damage may increase susceptibility to bacterial and viral infections, and this may be the main reason for the increased risk of pulmonary inflammation [ 19 , 20 ]. Based on previous research, it was stated that T2DM had a significant relationship with the mortality of COVID-19 patients, where T2DM patients infected with COVID-19 had a mortality risk of 1.75 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that about 20% of patients with kidney disease and comorbidity had a 3-fold higher risk of contracting viral infection than those without CKD. Furthermore, patients with acute kidney injury (AKI) who tested positive for COVID-19 had a higher risk of CKD [ 44 ] than those who did not have AKI [ 45 ], recognizing CKD plays a key role in the severity of COVID-19.…”
Section: Covid-19 In Renal Disease Patientsmentioning
confidence: 99%
“…The incidence of CKD increases with age, and 38% of the patients with CKD are more than 65 years old ( 77 ). Cardiovascular causes are recognized as the leading cause of death, accounting for 50%of the mortality in the CKD population ( 78 ).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Therefore, it is of great importance to investigate the cardiovascular injuries in the elderly with CKD induced by the pandemic COVID-19 infection. A comprehensive review reveals the effect of CKD on increased hospitalization and mortality of COVID-19, perhaps owing to immune dysfunction and increased susceptibility to infections ( 77 , 79 ).…”
Section: Comorbiditiesmentioning
confidence: 99%